HUBUNGAN PEMBERIAN TUNJANGAN SERTIFIKASI GURU DENGAN MOTIVASI DAN DISIPLIN KERJA GURU SMP DI OKSIBIL KABUPATEN PEGUNUNGAN BINTANG - Elisabeth Nawipa (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
This study uses hypothesis testing with multiple regression and partial regression analysis. Multiple regression is used to test the fourth hypothesis concerning the relationship of giving certification allowance to motivation and work discipline of teacher, while for hypodesis testing one, two and three used partial test, that is to know relation of giving of certification allowance with motivation and relation giving certification allowance to discipline teacher work and motivational relationships and work discipline of teachers. The results showed that there was a relationship between certification allowance with motivation with significance value of 0.444 with medium category. There is a relationship between certification allowance and teacher work discipline with significance value of 0.469 with medium category. There is a relationship between motivation and discipline of junior high school teachers in Oksibil Pegunungan Bintang Regency with a significance value of 0.661 with strong category. There is a correlation between certification allowance with motivation and discipline of junior high school teacher in Oksibil Pegunungan Bintang Regency 0,502 with medium category. Keywords: Provision of Teacher Certification Allowance, Motivation, Teacher Work Discipline